Pemanfaatan Limbah Tandan Kosong dari Industri Pengolahan Kelapa Sawit untuk Papan Partikel dengan Perekat Penol Formaldehida Utilization of Empty Fruit Bunch Waste from Oil Palm Industry for Particleboard Using Phenol Formaldehyde Adhesive - Bambang Subiyanto; Subyakto Subyakto; Sudijono Sudijono; Mohamad Gopar; Sasa Sofyan Munawar (Masyarakat Peneliti Kayu Indonesia, 2004)
Empty Fruit Bunch (EFB) is waste from oil palm industry that has potential to be used as particleboard material. Production of particleboard might be useful to decrease the waste from oil palm industry. The problem in using waste from oil palm is the high extractive content that can decrease adhesive properties in panel production using thermoplastic adhesive, cement or thermosetting adhesive. The problem can be solved by special treatment to oil palm waste to decrease the extractives content. The objective of this research is to observe the influence of some treatments of EFB, density and adhesive content on the physical and mechanical properties of particleboard using phenol formaldehyde adhesive. Adhesive content used were 8%, 10% and 12% from oven dry weight of particles, while density was varied at 0.6 g/cm3, 0.7 g/cm3, and 0.8 g/cm3. Pre-treatment for EFB particles were cold water soaking for 24 hours, hot water boiling for 2 hours, Ca(OH)2 1 % solvent boiling for 2 hours and NaOH 1 % solvent boiling for 2 hours.The results showed that cold water soaking treatment for 24 hours and hot water boiling for 2 hours was the optimum treatment. The optimum content of adhesive was 10% with minimum density of 0.7 g/cm3. Thickness swelling for all type of EFB particleboards were not met the JIS A-5908, while internal bond, screw withdrawal and modulus of rupture (MOR) were met the type 8 of JIS A-5908 (1994).